Pathogenesis and Management of COVID-19 - Khalid O. Alfarouk; Sari T. S. AlHoufie; Samrein B. M. Ahmed; Mona Shabana; Ahmed Ahmed; Saad S. Alqahtani; Ali S. Alqahtani; Ali M. Alqahtani; AbdelRahman M. Ramadan; Mohamed E. Ahmed; Heyam S. Ali; Adil Bashir; et al. (MDPI AG, 2021)
COVID-19, occurring due to SARS-COV-2 infection, is the most recent pandemic disease that has led to three million deaths at the time of writing. A great deal of effort has been directed towards altering the virus trajectory and/or managing the interactions of the virus with its subsequent targets in the human body; these interactions can lead to a chain reaction-like state manifested by a cytokine storm and progress to multiple organ failure. During cytokine storms the ratio of pro-inflammatory to anti-inflammatory mediators is generally increased, which contributes to the instigation of hyper-inflammation and confers advantages to the virus. Because cytokine expression patterns fluctuate from one person to another and even within the same person from one time to another, we suggest a road map of COVID-19 management using an individual approach instead of focusing on the blockbuster process (one treatment for most people, if not all). Here, we highlight the biology of the virus, study the interaction between the virus and humans, and present potential pharmacological and non-pharmacological modulators that might contribute to the global war against SARS-COV-2. We suggest an algorithmic roadmap to manage COVID-19.